Urban Climate Change Mitigation, Adaptation, and Disaster Risk Reduction – a Review on their joint use for Spatial Resilience - Trabucco, Isabella; Cristiano, Silvio (Contesti. Città, territori, progetti, 2026)
An increasing number of catastrophic events was recorded in the first two decades of the 21st century compared to the previous twenty years. The ongoing climate crisis suggests more disasters will happen, while other existing crises (ecological, energy, resources, socio-economic, geo-political, etc.) cannot be disregarded while trying to anticipate and handle them, both as possible concauses and as crucial factors in tackling them over time. Among different models and paradigms to address an uncertain era, Disaster Risk Reduction (DRR) and Climate Mitigation and Adaptation (CMA) represent two major categories aimed at inspiring urban and regional strategies, planning, and design options to pursue (climate-related) spatial resilience. This article presents a novel systematic literature review conducted through a Scopus-based query and subsequent qualitative content analysis, to understand how DRR and CMA are dealt with together in spatial planning, governance, and design, and to critically assess the depth, coherence, and disciplinary orientation of this integration. Findings highlight a fragmented and technocentric landscape, where DRR and CMA are frequently treated in parallel and rarely embedded in spatially grounded, participatory, or systemic frameworks. The review identifies significant gaps in disciplinary engagement — especially from planning, design, and political ecology — and proposes the need for a more transdisciplinary and situated understanding of spatial resilience. The literature review is ultimately aimed at providing new knowledge to strengthen DRR and CMA joint use for spatial resilience.